Practical Realization of Only Active Floating Lossless Inductance Simulator - Natchanai Roongmuanpha; Sumalee Unhavanich; Tattaya Pukkalanun; Worapong Tangsrirat (My University, 2024)
This paper describes an electronically controllable floating lossless inductance simulator circuit implemented with only off-the-shelf available integrated circuits, namely LT1228 and operational amplifier (OA). The proposed design consists solely of two LT1228s and a single OA. By using an active element named LT1228, the equivalent inductance can be tuned electronically with depended on the externally supplied current applied to LT1228. The proposed simulator imposed just one component matching restriction that required the equality of two transconductances. It is easily attainable with a simple current mirror. The worthiness of the proposed floating inductance simulator has been proven and applied to the construction of the 2nd-order RLC highpass/bandpass filter as an application. PSPICE simulations are used to investigate the characteristics of the proposed simulator and its filter realization.
Keywords: Magnetic Field Sensors Techniques; Advanced DC-DC Converters; Induction Heating and Inverter Technology